Adventures in Volcanoland: What Volcanoes Tell Us About the World and Ourselves - Scarpati, Claudio (Geologos, 2024)
Adventures in Volcanoland: What Volcanoes Tell Us About the World and Ourselves by Tamsin Mather, 2024. ABACUS books, 368 pages. Hardcover price € 30.79, paperback prize € 13.08, eBook price € 3.99, ISBN: 978-1408714614